Evaluation of Design Parameters on Drying of Kiwi Fruit - Ozgen, Filiz; Celik, Nevin (Mdpi, 2019)
In this study, the drying of kiwi fruit in a convective dryer is examined experimentally. Air velocity, thickness of the slices and drying time are the varied parameters in drying process. In the experimental study, kiwi slices having thickness of 4 and 8 mm are dried in the dryer under the conditions of 45 degrees C temperature of the drying air, 10% relative humidity and 0.5-1.5 m/s drying air velocity. In addition to the tests, the effects of mentioned drying parameters on drying are analyzed by ANOVA (Analysis of Variance) method to find the contribution rate of each parameter. For this aim, an orthogonal array is arranged by using Taguchi design of experiment method. As the results of experiments and variance analysis, it has been determined that, drying air velocity plays a significant effect on total drying time. The minimum drying time (225 min) is achieved for 1.5 m/s for 4 mm slices, and the maximum drying time (750 min) is achieved for 0.5 m/s for the kiwi sample sliced 8 mm thick. It is also concluded that, working with the convective dryer at different velocities is advantageous in terms of preserving brightness and color quality.
Keywords: drying; kiwi; air velocity; slice thickness